Application of Sol-gel Method and Co-Precipitation in the Material Synthesis Process of Magnetite Fe3O4 Nanoparticles - Maulinda; TM Zulfikar; Ismet; Vera Viena; Elvitriana (Proceeding of International Conference on Multidisciplinary Research, 2024)
The development of lithium batteries is one type of research that continues to be developed. Recently, lithium batteries have become the most widely used source of electrical energy as raw materials for the manufacture of lithium batteries. This study aims to compare the synthesis with Co precipitation and sol-gel methods as electrodes in lithium batteries. Nanosized particles were characterized for characterization using (X-ray fluorescence (XRF) and scanning electron microscopy-energy dispersive X-ray (XRD) and (SEM) -EDS). Based on the XRF characterization test, the results showed that the chemical composition of Magnetite Fe3O4 contained in the iron sands of the Syiah Kuala beach showed material purities of 87.10%, 86.73%, and 81.42% (Magnetite Separation). This shows that the synthesis of Fe3O4 using the sol-gel method yields results with better material purity than the coprecipitation method. The results of the SEM-EDS characterization test observations were based on particle analysis and the distribution observed on the surface morphology of the particles, where the sol-gel method provided precise results for the synthesis of Fe3O4 magnetite nanoparticles. The results of the characterization test based on the EDS analysis based on the EDS test obtained the amount of Fe3O4 of 70.00%, this indicates that the composition of iron provides a high value compared to other components contained in it